ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENABUNG MAHASISWA PADA BANK SYARIAH - Sucianto, Primadany Yusuf; M. Umar Burhan (Islamic Economics and finance in Focus, 2023)
This study aims to examine the effect of saving interest of Islamic Economics students of Universitas Brawijaya on Sharia Banks. This study uses Attitude variables, Subjective Norms, and Behavioral Control as factors that influence interest in saving at Islamic banks. The sampling method uses probability sampling with the Proportional Random Sampling metahod. The research sample consisted of 100 students of Islamic Economics class of 2017-2019 who were randomly selected. The results showed that attitudes had a significant positive influence on students' interest in saving at Islamic banks, subjective norms also had a significant effect on students' interest in saving at Islamic banks, but behavioral control did not have a significant influence on students' interest in saving at Islamic banks. So the conclusion can be drawn is that subjective attitudes and norms are important factors in influencing the interest of Islamic Economics students to save at Islamic banks. However, behavioral control did not make a significant contribution to this.